PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA KARYAWAN PADA PT. XYZ - Teguh Hendra; Aai Mustika (Komunitas Manajemen Kompetitif, 2026)
Essentially, every organization requires a workforce with good work discipline. To achieve this good work discipline, leaders or heads of an institution must be able to supervise their employees' work performance and identify and monitor errors made by employees in carrying out their assigned tasks. This study aims to determine the effect of supervision on employee work discipline at PT. XYZ, with a sample of 87 employees. The results of a simple linear regression test yielded a value of Y = 18.035 + 0.476X. The t-test hypothesis test results showed that the calculated t-value (4.374) was greater than the t-table value (1.988) with a significance level of 0.000 < 0.05, indicating that supervision influences work discipline. The coefficient of determination (R2) test yielded a value of 0.184, or 18.4%. The remaining 81.6% (100-18.4) was influenced by other variables not examined in this study. Therefore, this study concludes that supervision influences employee work discipline at PT. XYZ